1988
DOI: 10.1080/00913847.1988.11709665
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Dance Injuries Among Instructors and Students

Abstract: In brief: Aerobic dancing is a popular fitness activity in Japan, primarily among young women. To identify and characterize the injuries associated with aerobic dance, 161 instructors and 800 students from 13 Japanese fitness facilities were surveyed. Results showed an injury rate of 72.4% for instructors and 22.8% for students. The lower leg and foot were the most common injury sites for instructors and students, respectively. Though these results seem to indicate that aerobic dance is hazardous, the number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

1992
1992
2001
2001

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 7 publications
0
9
0
1
Order By: Relevance
“…This compares favourably with the ®ndings of a previous popmobility study in which heart rate was also shown to be an appropriate indicator of intensity when the percentage heart rate reserve was compared with % O 2 max (Grant et al 1993). Studies by Mutoh et al (1988) and Williford et al (1989) indicate that heart rate is not a good indicator of exercise intensity in LIP sessions. For example, an individual analysis of the heart rates in the Williford et al (1989) study indicates that some of the subjects were working at a heart rate approaching their maximum without any undue exhaustion or discomfort.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This compares favourably with the ®ndings of a previous popmobility study in which heart rate was also shown to be an appropriate indicator of intensity when the percentage heart rate reserve was compared with % O 2 max (Grant et al 1993). Studies by Mutoh et al (1988) and Williford et al (1989) indicate that heart rate is not a good indicator of exercise intensity in LIP sessions. For example, an individual analysis of the heart rates in the Williford et al (1989) study indicates that some of the subjects were working at a heart rate approaching their maximum without any undue exhaustion or discomfort.…”
Section: Discussionmentioning
confidence: 95%
“…Despite the popularity status of aerobic dance and its associated physiological bene®ts, this HIP style has been shown to result in overuse injuries caused by repeated stress to the legs, hips and lower back (Rothenberger et al 1988). A number of studies (Vetter et al 1985;Garrick et al 1986;Mutoh et al 1988) have shown that in aerobic dance 80% of injuries are caused by overuse.…”
Section: Introductionmentioning
confidence: 96%
“…The most common injuries associated with aerobic dance are overuse injuries to the foot and lower leg (83,84). In a survey of 800 aerobic dance participants in Japan, results showed a 22.8% injury rate or 0.15 injuries per 100 hours of participation (84).…”
Section: Arthritis Care and Researchmentioning
confidence: 99%
“…1,[6][7][8][9][10] The injury rate may be indicative of the high-impact forces that aerobic dance movements produce over a period of time. 1,[6][7][8][9][10] The injury rate may be indicative of the high-impact forces that aerobic dance movements produce over a period of time.…”
mentioning
confidence: 99%